The effects of Nigella sativa on sickness behavior induced by lipopolysaccharide in male Wistar rats - Fatemeh Norouzi; Azam Abareshi; Akbar Anaeigoudari; Mohammad Naser Shafei; Zahra Gholamnezhad; Mohsen Saeedjalali; Reza Mohebati; Mahmoud Hosseini (Avicenna Journal of Phytomedicine, 2016)
Objective: Neuroimmune factors contribute on the pathogenesis of sickness behaviors. Nigella sativa (NS) has anti-inflammatory, anti-anxiety and anti-depressive effects. In the present study, the effect of NS hydro-alcoholic extract on sickness behavior induced by lipopolysaccharide (LPS) was investigated. Materials and Methods: The rats were divided into five groups (n=10 in each): (1) control (saline), (2) LPS (1 mg/kg, administered two hours before behavioral tests), (3-5) LPS-Nigella sativa 100 , 200 and 400 mg/kg (LPS-NS 100, LPS-NS 200 and LPS-NS 400, respectively). Open- field (OF), elevated plus maze (EPM) and forced swimming test (FST) were performed. Results: In OF, LPS reduced the peripheral crossing, peripheral distance, total crossing and total distance compared to control (pConclusion: The results of the present study showed that the hydro-alcoholic extract of NS reduced the LPS-induced sickness behaviors in rats. Further investigations are required for better understanding the responsible compound (s) and the underlying mechanism(s).